(untitled) (Journal of Interdisciplinary Insights, 2023)
The translation of metaphors remains a significant challenge in the field of linguistics. The present study endeavors to bring fresh perspectives to this complex problem by examining the cognitive processing dynamics involved in the sight translation of metaphorical constructions from Chinese to English. Our analytical framework is the Conceptual Blending Theory (CBT), with we analyzed emergent structures generated within the metaphor blending space, revealing the intricate cognitive processes that underpin translation. We employed reaction time as a pivotal measure to gauge the efficiency and fluidity of the blending process. This metric serves as a real-time indicator of the cognitive load and complexity associated with metaphor translation. Furthermore, our study offers an exploration of the diverse strategies utilized for the translation of metaphorical constructions. These strategies, mapped from the analysis of reaction time and emergent structures, not only underscore the complexity of metaphor translation but also highlight potential areas for improvement and optimization in the sight translation process. The findings underscore a conspicuous absence of conceptual blending during the sight translation of metaphorical constructs. This is illustrated by the similarity in the mean values derived from the samples of two distinct groups. This commonality suggests that the translation process lacks a nuanced blend of original and target language elements, which is pivotal for an authentic translation. Furthermore, our results indicate an aberration in the formation of emergent structures within the blend space of metaphorical blending. This aberration is manifested in the form of excessive omission translation, free translation, and literal translation. These excessive proportions of various translation types suggest a departure from ideal translation practices, which aim for a balanced synthesis of literal and interpretive elements. This study provides valuable insights into the role of conceptual blending in the sight translation of metaphorical constructions. The identified deficiencies in the process pave the way for future research to develop more effective translation strategies that can deliver higher fidelity translations.